On exponential stability of composite stochastic control systems - Abedi, Fakhreddin; Leong, Wah June (Hindawi Publishing Corporation, 2013)
New results for exponential stability in probability of a composite stochastic control system are established. The main results of this paper enable us to derive sufficient conditions for exponential stability in r-th mean and almost sure exponential stability in probability of composite stochastic control system. Two numerical examples are given to illustrate the results.